Transformational Leadership and Organizational Climate from Teachers’ Perspectives (A Qualitative Study at School Tahfidz Durrotul Ummah, Mekar Jaya Village, Panongan District, Banten Province) - Hardian, Dafyar Eliadi; Sapta, Adea; Fadhilah, Syukran; Kewas, Horjel Gabriel (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Transformational Leadership and Organizational Climate from Teachers’ Perspectives (A Qualitative Study at School Tahfidz Durrotul Ummah, Mekar Jaya Village, Panongan District, Banten Province) This research investigates how teachers perceive the principal’s transformational leadership and the organizational climate at Tahfidz Durrotul?Ummah School in Mekar?Jaya?Village, Panongan District, Banten Province. Adopting a qualitative case?study design, the study gathered data through semi?structured interviews, participant observation, and document review, with five teachers serving as key informants. Analysis proceeded through data reduction, data display, and inductive interpretation. Findings show that teachers regard the principal as a transformational leader who models exemplary conduct, offers individualized encouragement, and sparks positive shifts in instructional practice. The organizational climate is portrayed as collegial, characterized by open communication, harmonious relationships, and mutual trust. Participants believe the combination of inspirational leadership and a supportive work environment greatly enhances their morale and professional growth. These results underscore the pivotal role of leadership and organizational culture in cultivating a healthy educational ecosystem, particularly within faith?based institutions such as tahfidz schools.